Diseño de un manual de prevención de riesgos en caso de catástrofes naturales en la escuela “Manuel Matheu” de la parroquia Pastocalle del cantón Latacunga en el año lectivo 2013-2014 - Toapanta Toapanta, Nancy Marlene (2015)
This research was conducted at "Manuel Matheu" school during the period 2013-2014; in which the entire educational community involved, taking into account risk prevention in natural disasters situations in children, parents and teachers at “Manuel Matheu” school. The research importance motivated in knowing and preventing risks that present in the educational community creating risk prevention strategies to avoid accidents inside or outside the institution to support the teachers and children through videos, seminars and drills ,etc. At “Manuel Matheu” school did not have a Risk Prevention Manual for natural disasters inside the institution….